The persecution of the Catholic Church in German-occupied Poland : reports presented to pope Pius XII, Vatican broadcasts and other reliable evidence (London : Burns Oates, 1941)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Katholieke Kerk; Wereldoorlog 2; Polen